Analysis of Heat Transfer of Fiber Mesocarp of Palm Oil (Elaeis Guineensis Jacq) as Roof Building - Istianto Budhi Rahardja; Rikman Rikman; Anwar Ilmar Ramadhan (Journal of Applied Sciences and Advanced Technology, 2018)
Palm oil fibers are waste products from Palm Oil Mill which is in the form of debris, solid, length of 3-4 cm, contained in coconut fruit (mesocarp) meat. Fiber roof building is the result of utilization of palm fiber waste as a roof of a building that is used to reduce heat from sunlight or from heat sources, so it is not directly exposed to humans and the surrounding environment. Fiber roof building is made by arranging the fiber in the mold and arranged in accordance with the dimensions to be made. To bind between fibers, used resin that has been mixed with the catalyst material, so easy to dry quickly. The ratio between resin and fiber is 1: ¼. The result of conduction heat conduction test that has been done on the fiber test object can reduce the highest heat of 125 °C and the lowest is 109 °C from the given heat source of 200 °C. This shows that palm fiber can be used as a heat reducer for buildings.